Children's relationships with brands: intergenerational and transgressions. Issue 1 (16th December 2019) - Chaudhary, Monica; Lopez, Alberto; Rodriguez, Rachel
Abstract : Purpose: The purpose of this paper is to understand and explore how young children relate to brands. The paper specifically attempts to explore their favourite and everyday brands with which they interact, understand the phenomenon of intergenerational transfer of brands, and study how child consumers experience and cope with brand transgressions. Design/methodology/approach: This is a qualitative study where 20 in-depth interviews were conducted among young Indian children in the age-group of 8–12 years. For data analysis "iterative method" is used. Inspiration was taken from Spiggle's (1994), Ereaut's (2002) and Holt and Thompson (2004). Findings: Children's relationships with brands are mainly characterised by four categories: their favourite brands, everyday brands, intergenerational brands and brand transgressions. Children's favourite brands can be categorised in fantasy, yummy, identity construction, social bonding, technology and trusted brands. Parents have a big influence on kids' lives leading to intergenerational brand-transfer. Children consumers also reveal having experience brand transgressions, more importantly, they also show signs of brand forgiveness. Originality/value: This qualitative study has addressed the pressing need to understand child understands of brands. This is one of the very few empirical studies that have investigated child consumer behaviour regarding their association with brands.